Role of Renal Prostaglandins in Sympathetically Mediated Renin Release in the Rat - Campbell, William B.; Graham, Robert M.; Jackson, Edwin K. (The Journal of Clinical Investigation, 1979)
Renal prostaglandins (PG) appear to mediate renin release due to stimulation of the intrarenal baroreceptor, but not that due to activation of the macula densa. However, as the role of PG in sympathetically mediated renin release remains unclear, a possible interrelationship between these factors was examined in conscious rats. Hydralazine increased the serum renin levels from 3.1±0.8 to 16.7±3.0 ng/ml per h at a dose of 1 mg/kg. Indomethacin (5 mg/kg) suppressed urinary PGE2 and PGF2α excretion by 89 and 74%, respectively, arachidonate hypotension by 82%, and inhibited the elevated renin levels from hydralazine by 100% without altering the hypotensive effect of the drug. Another PG synthetase inhibitor, meclofenamate, was also effective in attenuating hydralazine-induced renin release, urinary PGE2 and PGF2α excretion, and arachidonate hypotension. Isoproterenol, a nonselective beta-adrenergic agonist, increased heart rate, lowered blood pressure, and also stimulated the release of renin when administered intraperitoneally. However, intrarenal infusion of the drug only resulted in increased renin release. Indomethacin inhibited isoproterenol-induced renin release by 66 and 67%, respectively, without altering the hemodynamic effects associated with the intraperitoneal administration of the drug. The selective beta1 agonist, H133/22, increased the release of renin and heart rate in a dose-related manner without altering blood pressure. H133/22-induced renin release was inhibited by 80% by indomethacin pretreatment. Finally, intrarenal infusions of dibutyryl cyclic AMP (3 mg/kg per min) increased the serum activity from 4.1±0.2 to 20.4±3.9 ng/ml per h without altering mean arterial pressure. Indomethacin inhibited this renin response to dibutyryl cyclic AMP by 96%. Thus, renal PG appear to be important mediators of sympathetically stimulated renin release acting as a site distal to the beta-adrenergic receptor.